2022
DOI: 10.3390/jpm13010011
|View full text |Cite
|
Sign up to set email alerts
|

Nomogram for Predicting Semen Parameters Improvement after Microscopic Varicocelectomy in Infertile Men with Abnormal Semen Parameters

Abstract: Objectives: Information on the prediction of improved semen parameters following varicocelectomy is scarce and mostly contradictory. Therefore, we developed and validated a nomogram to predict whether abnormal semen parameters in infertile men could improve following microscopic varicocelectomy (MSV). Methods: From January 2018 to December 2021, 460 consecutive patients who underwent MSV were included. Of them, 336 patients as a development cohort at the Xiang Hua institution. As a validation cohort, Hu Nan Ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 23 publications
(27 reference statements)
0
1
0
Order By: Relevance
“…It is applicable not only for natural conception, but also for intrauterine insemination and in vitro fertilization [38] , [39] . Liu and colleagues' [40] research on total sperm count revealed a significant correlation between an increase in preoperative total sperm count and postoperative improvements, suggesting that the total sperm count holds a predictive value for postoperative semen condition assessment. In addition, Wang et al [41] showed that patients with a higher baseline sperm count after varicocele surgery had a more significant improvement in sperm parameters, and the improvement gap was positively correlated with the improvement in total sperm count after varicocele surgery.…”
Section: Discussionmentioning
confidence: 99%
“…It is applicable not only for natural conception, but also for intrauterine insemination and in vitro fertilization [38] , [39] . Liu and colleagues' [40] research on total sperm count revealed a significant correlation between an increase in preoperative total sperm count and postoperative improvements, suggesting that the total sperm count holds a predictive value for postoperative semen condition assessment. In addition, Wang et al [41] showed that patients with a higher baseline sperm count after varicocele surgery had a more significant improvement in sperm parameters, and the improvement gap was positively correlated with the improvement in total sperm count after varicocele surgery.…”
Section: Discussionmentioning
confidence: 99%